Unlocking Histatin Potential against Candida albicans and Streptococcus mutans Biofilms: Targeting the Extracellular Matrix While Preserving Oral Cell Integrity - Dias, Luana Mendonça [UNESP]; Marin, Lina M.; Pavarina, Ana Claudia [UNESP]; Siqueira, Walter L. (American Chemical Society (ACS), 2025)
Denture stomatitis affects up to 60% of prosthesis users due to biofilms mainly composed of Candida albicans and Streptococcus mutans, which persist the treatments because of their resilient extracellular matrix (ECM). This study tested four proteins/peptideshistatin 3 (His3), histatin 5 (His5), DR9-RR14, and RR14on these mixed biofilms grown on acrylic resin. Using previously determined biofilm inhibitory concentrations (BIC-2), their effects on biofilm viability, ECM components (proteins, extracellular DNA, and polysaccharides), and biofilm structure were assessed. His3 and His5 were the most effective, reducing biofilm cells by 46 and 41% and significantly decreasing ECM components. DR9-RR14 and RR14 had moderate effects. Imaging confirmed that His3 and His5 disrupted the biofilm structure. Cytotoxicity tests showed that all proteins/peptides were safe for gingival fibroblasts. Among the proteins/peptides evaluated, His3 showed the highest effectiveness, making it a promising candidate for preventing biofilm formation and ECM maturation, suggesting its potential use in treating denture stomatitis.